Variations in Greater Trochanter Height as a Relation to Patient Demographics: Implications for Femoral Nail Design - Jordan A. Haber; Amogh I. Iyer; Matthew Dulas; Douglas Weaver; Jason A. Strelzow (Advances in Orthopedics)
Intramedullary nail fixation is the “gold standard” for surgical intervention of femoral fractures. While many aspects of nail design and patient anatomy have received specific focus, anatomic variations in proximal femoral geometry and greater trochanteric height variation have been poorly studied. Understanding the potential relationship of the greater trochanter to patient demographics may provide an opportunity to improve implant placement. Retrospective review of x-ray and computed tomography images of the proximal femur was performed. Inclusion criteria consisted of skeletally mature patients over 18 years old with imaging of the proximal femur. Inclusion criteria identified 296 patients. Mean age of included patients was 34 ± 20 years. Average greater trochanter height was 40 ± 8.1 mm. Mean caput-collum-diaphyseal angle was 141 ± 8.6 degrees. After identifying significant factors using univariate analyses a multivariable linear regression demonstrated that patient height and caput-collum-diaphyseal angle were statistically significant predictors for greater trochanter height. For every 1 cm increase in patient height there was a predicted 0.11 mm increase in greater trochanter height (p=0.01). Conversely, every 1 degree increase in caput-collum-diaphyseal angle results in an associated 0.17 mm decrease in greater trochanter height (p<0.001). This study provides information that may allow for the potential optimization of implant design or implant position to minimize proximal nail protrusion, enhance nail fit and ensure cephalomedullary lag screw position in the head based on the proximal nail dimensions of the implant used.